Polymer phase change material and preparation method thereof

A polymer phase change material with high enthalpy and high heat resistance temperature was prepared by copolymerizing n-alkyl acrylate, di-n-alkyl maleate and α-olefin under solvent-free conditions. This solved the problem of insufficient enthalpy and heat resistance temperature in the existing technology and enabled the widespread application of cost-effective polymer phase change materials.

CN119264323APending Publication Date: 2025-01-07TIANJIN POLYTECHNIC UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411602817.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing polymer phase change materials have low enthalpy, insufficient heat resistance, high cost, and are easily soluble in water, making it difficult to meet the needs of various applications.

Method used

Using alkyl acrylate, dialkyl maleate, and α-olefin as raw materials, polymer phase change materials with high enthalpy and high heat resistance are prepared by free radical and atom transfer radical polymerization under solvent-free conditions, with the addition of chain transfer agents, heat stabilizers, and ultraviolet absorbers, and by vacuum polymerization.

Benefits of technology

We have developed polymer phase change materials with high enthalpy, high heat resistance, and high cost-effectiveness. The process is simple, the cost is low, the application range is wide, and the performance is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005128745850000011
    Figure HDA0005128745850000011
  • Figure HDA0005128745850000012
    Figure HDA0005128745850000012
  • Figure HDA0005128745850000021
    Figure HDA0005128745850000021
Patent Text Reader

Abstract

The invention discloses a polymer phase-change material and a preparation method thereof.The method for preparing the polymer phase-change material comprises the following steps that any two of a monomer A, a monomer B and a monomer C are mixed, under nitrogen protection, stirring is conducted, the temperature is raised to the initiating temperature of an initiator, then the initiator is added, and a mixture is obtained; adding one or more of a chain transfer agent, a heat stabilizer or an ultraviolet light absorber at the same time, and stirring for reaction; the monomer A is acrylic acid n-alkyl ester, the monomer B is maleic acid di-n-alkyl ester, and the monomer C is alpha-olefin. The method is free of reagents, simple in process, easy to control, high in production efficiency, wide in application range, low in cost and convenient for practical application, and the polymer phase change material prepared by adopting the method is excellent in thermal stability, relatively high in melt viscosity and relatively high in enthalpy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of phase change materials, and in particular to a polymer phase change material and a preparation method thereof. Background Art

[0002] Phase change materials can absorb or release a large amount of latent heat of phase change during the solid-liquid, solid-solid, liquid-gas and solid-gas phase change processes. They are a clean and recyclable energy storage material. They are widely used in agriculture, HVAC, construction, solar energy utilization and smart clothing, and their important role in implementing the "dual carbon" theory is becoming increasingly apparent. Phase change materials can be divided into three types: low temperature, medium temperature and high temperature according to the phase change temperature. The most widely used low-temperature phase change materials are n-alkanes, n-alkanols, n-alkanoic acids and fatty acid esters. Due to the low molecular weight and small interaction between molecules, the melt viscosity is generally very low, and it is very easy to flow and migrate in the liquid phase, causing environmental pollution and loss of function. In addition, the heat resistance temperature is low, making it difficult to meet some application needs. Polymer phase change materials have the characteristics of high melt viscosity and high thermal stability. Currently known polymer phase change materials are mainly aliphatic polyethers and aliphatic polyesters, such as polyethylene glycol, polybutylene glycol and polyhexamethylene glutarate, etc., with relatively few types. Polyethers are water-soluble and polyester raw materials are difficult to obtain. Due to factors such as phase change performance and price, their scope of use is also severely restricted.

[0003] Chinese invention patent publication number CN101798364A discloses a method for preparing a novel polymer phase change material - poly(meth)acrylate n-alkyl ester, which broadens the source of polymer phase change materials, but its thermal enthalpy and heat resistance temperature are relatively low, and sometimes it is difficult to meet the use requirements.

[0004] Chinese invention patent publication number CN104193865 A discloses a method for preparing polyethylene glycol n-alkyl vinyl ether. The product has good thermal stability and high thermal enthalpy and can be used as a polymer phase change material. However, it needs to be polymerized in a solvent and an anhydrous and oxygen-free cationic initiator is used to achieve this, which significantly increases the preparation cost.

[0005] Chinese invention patent publication number CN1616588A discloses a method for preparing a polymer phase change material, the structure of which is that an organic material with a low melting point and high phase change enthalpy is fixed on a high melting point or infusible skeleton through chemical bonds. Specifically, a polymer phase change material with two active end groups - polyethylene glycol and a polyethylene glycol with one active end group are fixed on a polymer skeleton material to form a three-dimensional network and comb-like mixed structure, so that it remains solid during the phase change process and has the characteristics of solid-solid phase change. However, this method has a low grafting rate, resulting in a low thermal enthalpy, and the heat resistance temperature is still low.

[0006] According to the known technology, the enthalpy of poly-alpha-olefin is low, and the effect of using as phase change material is not good. Because the monomer alpha-olefin is non-polar, poly-alpha-olefin can only be polymerized by Ziegler-Natta or metallocene catalyst, and the reaction needs to be carried out in anhydrous and oxygen-free environment, and the preparation conditions are extremely harsh, which also causes the cost to increase significantly. Maleic acid di-n-alkyl esters have failed to achieve large-scale production, and the price is very high. Although the enthalpy of poly-maleic acid di-n-alkyl esters is high, its melting temperature and crystallization temperature are quite different, which is not conducive to energy storage applications, and the thermal stability of its polymer is poor, and it cannot be used at higher temperatures. The enthalpy, heat stability and price of poly-alpha-olefins and poly-maleic acid di-n-alkyl esters are between. Summary of the invention

[0007] In view of the deficiencies of the prior art, an object of the present invention is to provide a polymer phase change material with high thermal enthalpy, high heat resistance temperature, high cost performance and insolubility in water.

[0008] Another object of the present invention is to provide a method for preparing the above-mentioned polymer phase change material, which has a simple process, is easy to control, has high production efficiency, low cost, and a wide range of applications and is convenient for practical application.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a polymer phase change material comprises the following steps:

[0011] Mix any two of monomer A, monomer B and monomer C, under nitrogen protection, stir and heat to the initiation temperature of the initiator, then add the initiator, and simultaneously add one or more of the chain transfer agent, heat stabilizer or ultraviolet absorber, stir and react for 3 to 10 hours; then heat to 160 to 220°C, reduce the pressure to 10 to 50 kPa for 2 to 4 hours, and then gradually reduce to room temperature to obtain a polymer phase change material, wherein,

[0012] The monomer A is n-alkyl acrylate;

[0013] The monomer B is di-n-alkyl maleate;

[0014] The monomer C is an α-olefin;

[0015] In a mixture of two monomers, the mass fraction of the monomer with the lowest content is not less than 10%;

[0016] The initiator is a free radical polymerization initiator, an atom transfer free radical polymerization initiator or a redox initiator, and the amount of the initiator is 0.1 to 1.5% of the total weight of the monomer;

[0017] In the above technical solution, the n-alkyl acrylate includes: n-dodecyl acrylate, n-tetradecyl acrylate, n-hexadecyl acrylate or n-octadecyl acrylate.

[0018] In the above technical solution, the di-n-alkyl maleate is di-n-dodecyl maleate, di-n-tetradecyl maleate, di-n-hexadecyl maleate or di-n-octadecyl maleate.

[0019] In the above technical solution, the α-olefin is 1-tetradecene, 1-hexadecene or 1-octadecene.

[0020] Although the purpose of the present invention can be achieved when the number of carbon atoms in the side chain of the polymer phase change material is an odd number, its monomer is not easy to obtain and is expensive, so it is not a preferred solution of the present invention.

[0021] In the above technical solution, the initiation temperature of the initiator is 60-80°C.

[0022] In the above technical solution, the atom transfer radical polymerization initiator is a mixture of cuprous bromide and methyl 2-bromopropionate, and the molar ratio of cuprous bromide to methyl 2-bromopropionate is (100-250):1.

[0023] In the above technical solution, the free radical polymerization initiator is benzoyl peroxide or azobisisobutyronitrile.

[0024] In the above technical solution, the redox initiator is a mixture of an oxidant and a reductant, the mass ratio of the oxidant to the reductant is 1:(2-6), the oxidant is ammonium persulfate, potassium persulfate or sodium persulfate, and the reductant is sodium bisulfite or sodium sulfate.

[0025] In the above technical solution, the amount of the initiator used is 0.3-1.0% of the total mass of the monomers.

[0026] In the above technical solution, the chain transfer agent is 2-mercaptoethanol, dodecyl mercaptan or dithioester, and the amount of the chain transfer agent is 0.1-3% of the total mass of the monomers.

[0027] In the above technical scheme, the heat stabilizer is 2,6-tert-butyl-4-methylphenol (antioxidant-264), pentaerythritol tetrakis(4-hydroxy-3,5-di-tert-butylphenylpropionate) (antioxidant-1010), 3,5-di-tert-butyl-4-hydroxyphenylpropionate octadecyl (antioxidant-1076), triphenyl phosphite (TPP) or trinonylphenyl phosphite (TNP), and the amount of the heat stabilizer is 0.1 to 3% of the total mass of the monomers.

[0028] In the above technical scheme, the ultraviolet absorber is 2-hydroxy-4-methoxybenzophenone (UV-9), 2-hydroxy-4-n-octyloxybenzophenone (UV-531), 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (UV-P), -benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid (UV-284), 2-(2-hydroxy-3,5-dibutyl-tert-phenyl)-5-chlorobenzotriazole (UV-327), p-tert-butylphenyl salicylate (TBS) or bisphenol A disalicylate (BAD), and the amount of the ultraviolet absorber is 0.1 to 3% of the total mass of the monomer.

[0029] In the above technical solution, the number average molecular weight of the polymer phase change material is above 10,000, the phase change temperature is 5-50°C, the thermal enthalpy is ≥68J / g, the 5% thermal weight loss temperature is 160-350°C, and the melt viscosity is greater than 100mPa.s.

[0030] In the above technical scheme, the temperature is raised to 160-220°C and the pressure is reduced to 10-50 kPa for 2-4 hours to promote the conversion rate and improve the uniformity of the distribution of polymer molecular chain length (molecular weight). At the same time, the pressure reduction treatment can reduce the content of small molecule impurities.

[0031] The method uses two monomers that can undergo free radical and atom transfer radical polymerization as raw materials, uses an initiator to initiate polymerization, and during the polymerization reaction, adds one or more of a chain transfer agent, a heat stabilizer or an ultraviolet absorber to react between the two monomers without using a solvent. A new type of polymer phase change material is prepared through reduced pressure distillation and direct polymerization reaction. Since the reaction is carried out under solvent-free conditions, there is no need for solvent recovery and washing and purification treatment.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The preparation method of the present invention uses two monomers as raw materials and directly obtains the polymer phase change material through polymerization reaction, without the need for grafting reaction, and without the need for skeleton support or coating materials. The process is simple and the preparation efficiency is high.

[0034] 2. The present invention fixes the side chain that can undergo phase change on the flexible polymer main chain, which overcomes the disadvantage of easy leakage of phase change materials and ensures the stability of performance.

[0035] 3. The present invention can achieve effective control of crystallization performance, price and thermal stability by adjusting the length of the polymer molecular chain (molecular weight) or adjusting the number of carbon atoms on the monomer side chain (using monomers with different numbers of carbon atoms in the side chain, such as n-dodecyl acrylate and n-tetradecyl acrylate), or using a copolymer of two different monomers, thereby avoiding the problem that the phase change temperature is difficult to meet the use requirements due to the use of only one phase change material. Therefore, a series of polymer phase change materials can be obtained that can meet the use requirements of different environments or uses.

[0036] 4. The polymer phase change material prepared by the present invention has excellent thermal stability, high melt viscosity, high cost performance and broad application prospects.

[0037] 5. The present invention adopts bulk polymerization and does not use solvents. It avoids the use of anhydrous and oxygen-free reaction conditions when preparing n-alkyl acrylate-α-olefin and n-alkyl maleate-α-olefin copolymers. It can also use lower-priced α-olefins to effectively reduce the price of polymer-type phase change materials, reduce costs, and improve the melt viscosity and thermal stability of polymer phase change materials, thereby reducing environmental pollution and reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The thermal spectrum of the polymer phase change material obtained in Example 1 measured by differential scanning calorimetry (DSC);

[0039] Figure 2 The thermal spectrum of the polymer phase change material obtained in Example 2 measured by differential scanning calorimetry (DSC);

[0040] Figure 3 The thermal spectrum of the polymer phase change material obtained in Example 3 measured by differential scanning calorimetry (DSC);

[0041] Figure 4 This is a thermal spectrum of the polymer phase change material obtained in Example 4 measured by differential scanning calorimetry (DSC). DETAILED DESCRIPTION

[0042] The scheme of the present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0043] Example 1

[0044] A method for preparing a polymer phase change material comprises the following steps:

[0045] Add 200g of tetradecyl acrylate (monomer A) and 80g of di-tetradecyl maleate (monomer B) to a round-bottom three-necked flask, and under nitrogen protection, heat to 70°C with magnetic stirring, add 1.0% of the total weight of the monomer as a free radical polymerization initiator azobisisobutyronitrile, 1.0% of the total weight of the monomer as a chain transfer agent dodecyl mercaptan, and 1.0% of the total weight of the monomer as a heat stabilizer 2,6-tert-butyl-4-methylphenol (antioxidant-264), stir and react for 4 hours, then heat to 220°C, and treat under reduced pressure at 10kPa for 4 hours, stop heating and stirring, and cool to room temperature under nitrogen protection to obtain a white solid. 13 C-NMR analysis and infrared spectrum analysis show that the white solid is tetradecyl acrylate-bis(n-tetradecyl)maleate copolymer. The number average molecular weight measured by gel permeation chromatography (GPC) is 40800, the weight average molecular weight is 94000, and the molecular weight distribution is 2.30.

[0046] Figure 1 The thermal spectrum of the polymer phase change material obtained in Example 1 measured by differential scanning calorimetry (DSC) is shown in FIG. Figure 1 It can be seen that the endothermic (melting) temperature of the polymer phase change material obtained in Example 1 is 25.9°C, the exothermic (crystallization) temperature is 10.2°C, and the thermal enthalpy is 91 J / g. Thermogravimetric analysis (TG) test shows that its 5% weight loss temperature is 287°C, and the melt viscosity at 200°C is 1050 mPa.s.

[0047] The tetradecyl acrylate-bis(n-tetradecyl maleate) copolymer prepared in this embodiment with a mass fraction of 99.0wt% was added with UV-531 with a mass fraction of 1.0wt% as the core component of the fiber, and polybutylene terephthalate was used as the sheath component of the fiber. After both components were dried to a moisture content of less than 150ppm, their mass ratio was controlled to be 30:70, and they were melt-extruded separately at 250°C, and composite spun using a 48-hole, 0.3mm-diameter spinneret. After cooling in a 18°C, 65% RH channel, they were stretched by secondary hot rollers at 80°C and 160°C for a total of 3.2 times, and wound at 3900m / min to form core-sheath composite filament fibers. The single fiber fineness was tested to be 3.8 dtex, the tensile breaking strength was 2.2 cN / dtex, and the breaking elongation was 33%; the endothermic temperature of the core-sheath composite filament fiber was 25.5°C, the exothermic temperature was 10.2°C, and the heat release was 25 J / g.

[0048] The core-sheath composite filament can be used for bedding fillings, thermal insulation linings for sports and leisure clothing, etc. Due to its characteristic of automatically adjusting the internal temperature of clothing, it can significantly improve comfort.

[0049] Example 2

[0050] A method for preparing a polymer phase change material comprises the following steps:

[0051] Add 200g of 1-hexadecene (monomer C) and 200g of tetradecyl acrylate (monomer A) to a round-bottom three-necked flask, and heat to 65°C with magnetic stirring under nitrogen protection, add 0.6% of the total weight of the monomer as a free radical polymerization initiator azobisisobutyronitrile and 0.5% of the chain transfer agent dodecyl mercaptan, stir and react for 6 hours, then heat to 160°C, decompress at 10kPa for 4 hours, stop heating and stirring, and cool to room temperature under nitrogen protection to obtain a colorless viscous liquid. 13 C-NMR analysis and infrared spectrum analysis showed that the colorless viscous liquid was tetradecyl acrylate-1-hexadecene copolymer. The number average molecular weight measured by GPC was 10300, the weight average molecular weight was 25200, and the molecular weight distribution was 2.45.

[0052] Figure 2 The thermal spectrum of the polymer phase change material obtained in Example 2 measured by differential scanning calorimetry (DSC) is shown in FIG. Figure 2 It can be seen that the endothermic (melting) temperature of the polymer phase change material is 5.2°C, the exothermic (crystallization) temperature is -6.4°C, and the thermal enthalpy is 110 J / g. TG test shows that its 5% weight loss temperature is 160.0°C, and the melt viscosity at 200°C is 106 mPa.s.

[0053] Example 3

[0054] A method for preparing a polymer phase change material comprises the following steps:

[0055] Add 200g of maleic acid bis(n-hexadecyl) ester (monomer B) and 200g of 1-hexadecene (monomer C) to a round-bottom three-necked flask, and heat to 80°C with magnetic stirring under nitrogen protection, add 0.3% of the total weight of the monomer as a free radical polymerization initiator benzoyl peroxide and 0.5wt% of the chain transfer agent 2-mercaptoethanol, stir and react for 8h, then heat to 200°C, and treat under reduced pressure at 10kPa for 4h, then stop heating and stirring, and cool to room temperature under nitrogen protection to obtain a white solid. 13 C-NMR analysis and infrared spectrum analysis showed that the white solid was maleic acid bis(n-hexadecyl)ester-1-hexadecene copolymer. The number average molecular weight measured by GPC was 41,000, the weight average molecular weight was 95,000, and the molecular weight distribution was 2.32.

[0056] Figure 3 The thermal spectrum of the polymer phase change material obtained in Example 3 measured by differential scanning calorimetry (DSC) is shown in FIG. Figure 3It can be seen that the polymer phase change material obtained in Example 3 has an endothermic (melting) temperature of 23.3°C, an exothermic (crystallization) temperature of 7.0°C, and a thermal enthalpy of 75 J / g. TG test shows that its 5% weight loss temperature is 235.0°C, and the melt viscosity at 200°C is 408 mPa.s.

[0057] Example 4

[0058] A method for preparing a polymer phase change material comprises the following steps:

[0059] Add 200g of octadecyl acrylate (monomer A) and 200g of dodecyl maleate (monomer B) to a round-bottom three-necked flask, and heat to 60°C with magnetic stirring under nitrogen protection, add 0.3% of the total weight of the atom transfer radical polymerization initiator (the atom transfer radical polymerization initiator is a mixture of cuprous bromide and methyl 2-bromopropionate, and the molar ratio of cuprous bromide to methyl 2-bromopropionate is 250:1), 0.5% of the chain transfer agent dodecyl mercaptan, stir and react for 8h, then heat to 180°C, decompress at 10kPa for 4h, stop heating and stirring, and cool to room temperature under nitrogen protection to obtain a light yellow liquid. 13 C-NMR analysis and infrared spectrum analysis showed that the light yellow liquid was octadecyl acrylate-dodecyl maleate copolymer. The number average molecular weight measured by GPC was 56,000, the weight average molecular weight was 113,000, and the molecular weight distribution was 2.02.

[0060] Figure 4 The thermal spectrum of the polymer phase change material obtained in Example 4 measured by differential scanning calorimetry (DSC) shows that the endothermic (melting) temperature of the polymer phase change material obtained in Example 4 is 21.5°C, the exothermic (crystallization) temperature is 5.4°C, and the thermal enthalpy is 69 J / g. The TG test shows that its 5% weight loss temperature is 170.0°C, and the melt viscosity at 200°C is 101 mPa.s.

[0061] 1.0wt% UV-P was added to the acrylate-dicetyl maleate copolymer prepared in this embodiment with a mass fraction of 99.0wt% as the island component of the fiber, and polylactic acid was used as the sea component of the fiber. After the two components were dried to a moisture content of less than 150ppm, their mass ratio was controlled to be 30:70, and they were melt-extruded separately at 215°C, and composite spun using a 48-hole, 0.3mm-diameter spinneret. After cooling in a 18°C, 65% RH channel, the fibers were stretched 3 times by hot rollers at 80°C and 120°C, and wound at 3500m / min to form core-sheath composite filament fibers with a single filament fineness of 3.1dtex, a tensile breaking strength of 2.1cN / dtex, and an elongation at break of 28%. The core-sheath composite filament fibers had an endothermic temperature of 38.1°C, an exothermic temperature of 23.0°C, and a heat release of 35J / g.

[0062] The core-sheath composite filament fiber can be used for bedding fillings, thermal insulation linings for sports and leisure clothing, etc. Due to the characteristic of automatically adjusting the internal temperature of clothing, it can significantly improve comfort.

[0063] Example 5

[0064] A preparation method of a polymer phase change material comprises the following steps: adding 200 g of n-dodecyl acrylate (monomer A) and 280 g of di-n-octadecyl maleate (monomer B) into a round-bottom three-necked flask, heating the mixture to 50° C. with magnetic stirring under nitrogen protection, adding a redox initiator (the redox initiator is a mixture of an oxidant and a reductant, the oxidant is 0.48 g of ammonium persulfate, and the reductant is 0.96 g of sodium bisulfite), 4.8 g of a chain transfer agent dodecyl mercaptan, and 4.8 g of a thermal stabilizer 2,6-tert-butyl-4-methylphenol (antioxidant-264), stirring the mixture for reaction for 4 hours, heating the mixture to 220° C., carrying out a reduced pressure treatment at 10 kPa for 4 hours, stopping heating and stirring, and cooling the mixture to room temperature under nitrogen protection to obtain a white solid.

[0065] use 13 C-NMR analysis and infrared spectrum analysis showed that the white waxy solid was a copolymer of n-dodecyl acrylate and n-octadecyl maleate. The number average molecular weight measured by GPC was 55,000, the weight average molecular weight was 94,000, and the molecular weight distribution was 1.71.

[0066] The DSC test results show that the endothermic (melting) temperature of the polymer phase change material obtained in Example 5 is 31.3°C, the exothermic (crystallization) temperature is 21.6°C, and the thermal enthalpy is 68 J / g. The TG test shows that its 5% weight loss temperature is 233°C and the melt viscosity is 10500 mPa.s.

[0067] Example 6

[0068] A method for preparing a polymer phase change material comprises the following steps:

[0069] 200 g of tetradecyl acrylate (monomer A) and 200 g of didodecanol maleate (monomer B) were added to a round-bottom three-necked flask. Under nitrogen protection, the temperature was raised to 60° C. with magnetic stirring. 0.3% of the total mass of the monomer was added as an atom transfer radical polymerization initiator (the atom transfer radical polymerization initiator was a mixture of cuprous bromide and methyl 2-bromopropionate, and the molar ratio of cuprous bromide to methyl 2-bromopropionate was 100:1), and 0.5% of the chain transfer agent dodecyl mercaptan were added. After stirring for 8 h, the temperature was raised to 180° C., and the pressure was reduced at 10 kPa for 4 h. The heating and stirring were stopped, and the temperature was lowered to room temperature under nitrogen protection to obtain a light yellow liquid.

[0070] use 13C-NMR analysis and infrared spectrum analysis showed that the light yellow liquid was tetradecyl acrylate-dodecyl maleate copolymer. The number average molecular weight measured by GPC was 28,000, the weight average molecular weight was 56,000, and the molecular weight distribution was 2.02.

[0071] The DSC test results show that the polymer phase change material obtained in Example 6 has an endothermic (melting) temperature of 11.5°C, an exothermic (crystallization) temperature of 1.6°C, and a thermal enthalpy of 72 J / g. The TG test shows that its 5% weight loss temperature is 186°C and the melt viscosity is 810 mPa.s.

[0072] Comparative Example 1

[0073] A method for preparing a polymer material comprises the following steps:

[0074] Weigh 1-tetradecene and n-heptane (the mass ratio of 1-tetradecene to n-heptane is 1:10), add anhydrous AlCl3 accounting for 1.0% of the mass of 1-tetradecene, and put them into a four-necked bottle dried by hot nitrogen. The reaction is carried out in a four-necked bottle Schlenk, mechanically stirred and magnetically sealed, and then washed with water equal to that of n-heptane at 110°C for 2h. After washing, move into a separating funnel, stand and separate, and then remove unreacted monomers and solvents by vacuum distillation (adding 2% carclazyte and 0.5% Na2CO3), and obtain oily liquid poly 1-tetradecene after filtration. The conversion rate is 93%, and the solvent loss rate is about 15%. GPC measured the number average molecular weight to be 4500, the weight average molecular weight to be 10200, and the molecular weight distribution to be 2.67. The endothermic (melting) temperature of poly 1-tetradecene is 7.5°C, the exothermic (crystallization) temperature is -5.0°C, and the thermal enthalpy is 45J / g. 5% thermal weight loss temperature is 380°C. 100°C poly-1-tetradecene dynamic viscosity is 88 mPa.s.

[0075] It can be seen from this comparative example that the preparation of poly-alpha-olefin alone requires the use of anhydrous and oxygen-free conditions and organic solvents, and the melt viscosity of poly-1-tetradecene is too low to be used for the preparation of smart fibers.

[0076] Comparative Example 2

[0077] A method for preparing a polymer material comprises the following steps:

[0078] Add purified maleic acid di-n-tetradecyl to a three-necked flask under nitrogen protection, heat to 65°C under mechanical stirring, add azobisisobutyronitrile accounting for 0.5% of the mass of maleic acid di-n-tetradecyl, and then add 2-mercaptoethanol accounting for 1% of the mass of maleic acid di-n-tetradecyl, react for 6 hours, heat to 200°C, and distill under reduced pressure to obtain poly maleic acid di-n-tetradecyl. GPC measured a number average molecular weight of 32500, a weight average molecular weight of 65000, and a molecular weight distribution of 2.00. The endothermic (melting) temperature of poly maleic acid di-n-tetradecyl is 30.2°C, the exothermic (crystallization) temperature is 4.7°C, and the thermal enthalpy is 100J / g. 5% thermal weight loss temperature is 220°C. The dynamic viscosity of poly(di-n-tetradecyl maleate) is 170 mPa.s at 100°C, and its melt viscosity is relatively high, so it can be used for smart fiber spinning. However, its exothermic temperature is low, and the difference between its melting temperature and crystallization temperature is too large, so it is difficult to find a matching usage scenario, and the use effect is poor.

Claims

1. A method for preparing a polymer phase change material, characterized in that: The following steps are involved: Mix any two of monomer A, monomer B and monomer C, under nitrogen protection, stir and heat to the initiator initiation temperature, then add the initiator, and simultaneously add one or more of the chain transfer agent, heat stabilizer or ultraviolet absorber, stir and react for 3 to 10 hours; then heat to 160 to 220°C, reduce the pressure to 10 to 50 kPa for 2 to 4 hours, and then gradually reduce to room temperature to obtain a polymer phase change material, wherein: The monomer A is n-alkyl acrylate; The monomer B is di-n-alkyl maleate; The monomer C is an α-olefin; In a mixture of two monomers, the mass fraction of the monomer with the lowest content is not less than 10%; The initiator is a free radical polymerization initiator, an atom transfer free radical polymerization initiator or a redox initiator, and the amount of the initiator used is 0.1-1.5% of the total weight of the monomers.

2. The preparation method according to claim 1, characterized in that: The n-alkyl acrylate is n-dodecyl acrylate, n-tetradecyl acrylate, n-hexadecyl acrylate or n-octadecyl acrylate; The di-n-alkyl maleate is di-n-dodecyl maleate, di-n-tetradecyl maleate, di-n-hexadecyl maleate or di-n-octadecyl maleate; The α-olefin is 1-tetradecene, 1-hexadecene or 1-octadecene.

3. The preparation method according to claim 1, characterized in that: The initiation temperature of the initiator is 60-80°C.

4. The preparation method according to claim 1, characterized in that: The atom transfer radical polymerization initiator is a mixture of cuprous bromide and methyl 2-bromopropionate, and the molar ratio of cuprous bromide to methyl 2-bromopropionate is (100-250):

1.

5. The preparation method according to claim 1, characterized in that: The free radical polymerization initiator is benzoyl peroxide or azobisisobutyronitrile; the redox initiator is a mixture of an oxidant and a reductant, the mass ratio of the oxidant to the reductant is 1:(2-6), the oxidant is ammonium persulfate, potassium persulfate or sodium persulfate, and the reductant is sodium bisulfite or sodium sulfate.

6. The preparation method according to claim 1, characterized in that: The amount of the initiator used is 0.3-1.0% of the total weight of the monomers.

7. The preparation method according to claim 1, characterized in that: The chain transfer agent is 2-mercaptoethanol, dodecyl mercaptan or dithioester, and the amount of the chain transfer agent is 0.1-3% of the total weight of the monomers.

8. The preparation method according to claim 1, characterized in that: The heat stabilizer is 2,6-tert-butyl-4-methylphenol, pentaerythritol tetrakis(4-hydroxy-3,5-di-tert-butylphenylpropionate), octadecyl 3,5-di-tert-butyl-4-hydroxyphenylpropionate, triphenyl phosphite or trinonylphenyl phosphite, and the amount of the heat stabilizer is 0.1-3% of the total weight of the monomers.

9. The preparation method according to claim 1, characterized in that: The ultraviolet absorber is 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, -benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid, 2-(2-hydroxy-3,5-dibutyl-tert-phenyl)-5-chlorobenzotriazole, p-tert-butylphenyl salicylate or bisphenol A disalicylate, and the amount of the ultraviolet absorber is 0.1-3% of the total weight of the monomers.

10. A polymer phase change material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The polymer phase change material has a number average molecular weight of more than 10,000, a melting temperature of 5 to 50° C., a thermal enthalpy of ≥68 J / g, a 5% thermal weight loss temperature of 160 to 350° C., and a melting viscosity of more than 100 mPa.s.

Citation Information

Patent Citations

  • Preparation method of polymer type phase change material

    CN101798364A

  • Polymer type phase change material and preparation method thereof

    CN104193865A

  • High molecular solid / solid phase changing material with net type and comb type mixed structure and its preparing method

    CN1616588A